Penerapan Model Cooperative Learning Tipe Stad Untuk Meningkatkan Kreativitas Belajar Siswa Kelas V SD - Servista Bukit; Ekayanti Tarigan; Rini Ramadhani (Tut Wuri Handayani : Jurnal Keguruan dan Ilmu Pendidikan, 2022)
This research is a classroom action research (Classroom Action Research) with the aim of increasing the learning creativity of fifth grade students at SDN 101835 Bngkawan on the subject matter of Civics by applying the STAD Type Cooperative Learning model for material unity and national unity T.A 2021/2022. This CAR uses the Kemmis and McTaggart model with the stages of research, namely planning, implementing actions and observing, reflecting. This study lasted for two cycles based on the results of reflections from the initial observations and the previous cycle with the object of research being the fifth grade students with 13 boys and 12 girls. Based on the results of the study, the percentage of students' learning creativity in the initial conditions was 55% with the category of Less Creative. After implementing the STAD Type Cooperative Learning model, the first cycle obtained the percentage of student learning creativity of 68.6% with the category of Creative Enough and in the second cycle the percentage of student learning creativity was obtained by 79.8 % in the Creative category.